Relationship Of Authoritary Parents Patterns (Authoritarian Parenting Style) Towards Aggressive Students 'Behavior And Its Implications In Counseling And Counseling Services - Gabriella Sagarmatha; Yeni Karneli (Jurnal Neo Konseling, 2020)
This research is motivated by the phenomenon of the number of students behaving aggressively, such as fighting, hitting, kicking, attacking, taunting others, disturbing classmates, fighting teacher's words, and violating school rules. Aggressive is a negative behavior which is thought to be one of the contributing factors is authoritarian parenting. This study aims to: (1) describe the authoritarian parenting of students, (2) to describe students 'aggressive behavior, and (3) to examine the relationship between authoritarian parenting and students' aggressive behavior. This research is a descriptive correlational research with quantitative methods. The population of this study were all students of SMP N 16 Padang totaling 791 people who were actively registered in the 2020/2021 school year. The total sample of 263 students was selected using the Stratified Proportional Random Sampling technique. The research instruments used were the authoritarian parenting style questionnaire and the student's aggressive behavior questionnaire. Data were analyzed using descriptive statistical techniques and Pearson Product Moment techniques with the help of SPSS For Windows 20.0. The results showed that (1) the students' authoritarian parenting style was in the high category (2) the students' aggressive behavior was in the high category, and (3) there was a significant relationship between authoritarian parenting and students' aggressive behavior with a correlation coefficient of 0.248 which was at 0.000 significance level with a very strong relationship level.. Based on the research findings, it is suggested that BK teachers or school counselors be able to provide guidance and counseling services, information services, individual counseling services, group counseling services to students, in order to help and minimize students falling into aggressive behavior. Furthermore, providing information and family counseling services to help minimize students' authoritarian parenting styles.